The value of being the decisive voter: Exploratory evidence from a hedonic model - Peters, Ethan; Hall, Joshua C. (Frontiers in Applied Mathematics and Statistics, 2023)
In the field of public economics, there is a literature on calculating the probability of being a decisive voter. The raison d'etre of this literature is to explain voter turnout. In this short empirical paper, we look at the question from a different angle. Heterogeneity in voting preferences means that some individuals vote rationally, others instrumentally, and some individuals are marginal and respond to changes in the probability of being decisive. Individuals with a preference for instrumental voting might be willing to pay more to live in an area with a greater probability of being a decisive voter. If this is the case, housing prices should reflect this higher willingness to pay. We test our theory using hedonic data from Columbus Ohio and find suggestive evidence that voters are willing to pay for a greater likelihood of being a decisive voter. Our results, however, cannot rule out other interpretations.